THE USE OF HYDROCARBON KIT TEACHING AIDS FROM USED MATERIALS IN TGT LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES AND MOTIVATION AT RURAL SCHOOL - Minarni Ramajura; Kasmudin Mustapa; Magfirah Magfirah (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2023)
This study aims to determine the effectiveness of the use of teaching aids hydrocarbon materials from used goods in learning with the TGT model to improve learning outcomes and student motivation at rural school. The research design used was a quasi-experimental design with a two-group posttest-only design. The research sample is 40 high school students in SMAN 9 Palu suburbs. Hydrocarbon teaching aids are in the form of KIT puzzles and molimod.. Hydrocarbon teaching aids have been validated by media experts and material experts and got very feasible result (91.5%). The research instrument used in this study was a test of hydrocarbon material and a learning motivation questionnaire. Data on learning outcomes and motivation were analyzed using descriptive statistics and inferential statistics independent sample t-test. The results showed that the use of teaching aids for hydrocarbon materials from used goods in learning with the TGT model was effective in improving student learning outcomes because there were differences in learning outcomes tcount (2.46) > ttable (2.02) and the experimental group learning outcomes were higher than the control class. There are differences in learning motivation tcount (3.17) > ttable (2.02), but the difference in motivation is very small so that the learning motivation in the experimental group and the control class is almost the same